The knowledge economy and socialism : science and society in Cuba - Lage Dávila, Agustín, 1949-; Lage Dávila, Agustín, 1949- (New York : Monthly Review Press, 2024)
""Cuba's future must, by necessity, be a future of scientists," Fidel Castro proclaimed in 1960. As Agustín Lage Dávila shows in this pathbreaking book, Cuba has in fact become a global leader in both the generation and application of scientific knowledge-as demonstrated by its ubiquitous production of socially useful products, from vaccines and medicines, to organic food. Speaking from his position as a noted Cuban immunologist, Dr. Lage shows how Cuba achieved such prominence, positing that the training of its scientists, their scientific practices, and their relationships with the Cuban people are intimately connected to the socialist culture that derived from the Cuban Revolution"--
Introduction -- Property and Expropriation in the Knowledge Economy -- Science and Culture: The Cultural Roots of Productivity -- The Knowledge Economy and Socialism: Reflections from the Cuban Biotechnology Experience -- The Knowledge Economy and Socialism: Reflections from Yaguajay -- Connecting Science and Economy: The Levers of Socialism -- Knowledge, Society, and National Sovereignty in the Twenty-First Century -- The Functions of Science in the Cuban Economic Model -- The High-Technology Company and the Management of Discontinuities -- Management in the High-Technology Company -- The Knowledge Economy and Socialism: An Opportunity for Development -- The Knowledge Economy and Socialism: Cuban Question.
Originally published in 2013 in Spanish as: La economía del conocimiento y el socialismo.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Knowledge economy -- Cuba; Socialism -- Cuba; Science -- Economic aspects -- Cuba; High technology industries -- Cuba; Cuba -- Economic policy; Research -- Cuba; Économie du savoir -- Cuba; Recherche -- Cuba; Sciences -- Aspect économique -- Cuba; Industries de pointe -- Cuba; Cuba -- Politique économique.; Cuba; Caribbean & West Indies; HISTORY; Political Economy; POLITICAL SCIENCE; Political Ideologies